Endoscopic retrograde cholangiopancreatography (ERCP) in critically ill patients is safe and effective when performed in the endoscopy suite - Farina, Domenico A.; Komanduri, Srinadh; Aadam, A. Aziz; Keswani, Rajesh N. (Endoscopy International Open, 2020)
Background and study aims Critically ill patients may require endoscopic retrograde cholangiopancreatography (ERCP) but performing ERCP in the intensive care unit (ICU) poses logistic and technical challenges. There are no data on ICU patients undergoing ERCP in the endoscopy suite. The primary aim of this study was to report outcomes, including safety, when ERCP in critically ill patients is performed in the endoscopy suite.Patients and methods We queried our institutional endoscopy database to identify all ICU patients who underwent ERCP at a single academic medical center from 04/01/2010 to 11/30/2017. Only patients admitted to an ICU prior to ERCP were included.Results Of 7,218 ERCPs performed during the study period, 260 ERCPs (3.6 %) were performed in 231 ICU patients (mean age 61y; 53 % male); nearly all ICU patient ERCPs (n = 258; 99 %) occurred in the endoscopy suite. ERCP indications included cholangitis (50 %), post-liver transplant cholestasis (15 %), and bile leak (10 %). All ERCPs were performed with anesthesiology, most with general anesthesia (60 %) and in the prone position (60 %). Most patients (73 %) had sepsis. Prior to ERCP, 17 % of patients required vasopressors; vasopressors were begun during ERCP in 4 %.The cannulation success rate was 95 % (94 % in native papillae). Adverse events occurred in 9 % (n = 23) of cases with post-ERCP pancreatitis most common. No patients died during or within 24 hours of ERCP. Mortality at 30 days was 16 %, all attributed to underlying disease.Conclusions When advanced ventilatory and hemodynamic support is available, critically ill patients can safely and effectively undergo ERCP in the endoscopy suite.